FACTORS ASSOCIATED WITH MORTALITY OF ELDERLY PATIENTS WITH COVID-19 INFECTION AT M. DJAMIL HOSPITAL, PADANG, WEST SUMATRA, INDONESIA : COVID-19 INFECTION - Mulyana, Roza; Elvira, Dwitya; Martini, Rose Dinda (STIKes Mandala Waluya Kendari, 2025)
Background: To analyze the factors influencing the mortality incidence of elderly patients with COVID-19 infection in Padang, West Sumatra, Indonesia. Methods: This is a retrospective study at M. Djamil Hospital, Padang. Data was collected from the medical records of COVID-19 patients treated during July-September 2021. Results: Of the 243 elderly patients who experienced COVID-19, the most deaths were male (58.6%) with an average age of 69.64 ± 7.74 years. Multivariate analysis showed that patients with critical-severe clinical symptoms (odds ratio (OR) 12.95; 95% confidence interval (CI) 6.66–25.19), heart disease (OR 6.94; 95% CI 1.63–29.60), respiratory rate ≥30 breaths per minute (OR 3.48; 95% CI 1.04–11.60), pulse ≥100 beats per minute (OR 2.88; 95% CI 1.03–8.04), using a ventilator or high-flow nasal cannula (OR 19.78; 95% CI 5.92–66.10), prothrombin time >13.16 second (OR 12.35; 95% CI 2.43–62.77), interleukin-6 >6 pg/mL (OR 15.19; 95%CI 2.53–91.26), and random blood glucose >199 mg/dL (OR 3.45; 95% CI 1.02–11.68) have a high risk of death. Conclusion: Elderly patients with COVID-19 infection with critical-severe clinical symptoms accompanied by heart disease, using ventilator or high-flow nasal cannula, longer prothrombin time, high level of interleukin-6, and random blood glucose have higher risk of mortality.